Even better than the real thing Whitney Biennial 2024 - Rothkopf, Scott 1976- (Whitney Museum of American Art, 2024)
A companion to the Whitney's signature exhibition, featuring artists who are shaping the conversation about contemporary art in the United States today. The curators of the 2024 Whitney Biennial, Chrissie Iles and Meg Onli, are both known for genre-defying, boundary-pushing thematic exhibitions A thematically organized image section reflecting the work of artists in the Biennial will be followed by entries about each artist--an approach that will encourage readers to draw connections between the work of different artists. A collaborative essay by Iles and Onli will present their thinking behind the exhibition, while essays by curators and scholars Eva Hayward and Amber Jamilla Musser will surface specific themes